Clinical Correlation of CD4 Count and Dry Eye Disease (DED) Severity Among HIV Patients: A Case Study in Voluntary Counseling and Testing Clinic Prof Ngoerah General Hospital, Bali: Oral Presentation - Observational Study - Resident - PUTU AYU WULANSARI (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Dry Eye Disease is a multi-factorial ocular surface and tear film instability disease. It has been reported as one of the most frequent anterior segment ocular manifestations in HIV patients, occurring late in the disease. The study aimed to investigate clinical correlation of CD4 count and severity of the disease. Methods : This study was a hospital based cross-sectional study where 75 HIV patients (150 eyes) aged 18-50 years old were referred to ophthalmology clinic in VCT for ocular surface related complaints and were included in the study. Results : The study showed significant moderate positive correlation between CD4 count with Tear Break Up Time (TBUT) (r-value=0.509;p-value=0.05) and negatively correlated with Ocular Surface Disease Index (OSDI) score (r-value=-0.252, p-value=0.035). There were a significant difference in CD4 count between mild and moderate dry eyes (p-value=0.005) and between mild and severe dry eyes (p-value=0.005), however no significant difference was observed between moderate and severe dry eyes (p value=0.435). The severity of dry eye in HIV patients also tends to differ in-between clinical stage of the disease (p value=0.513) and with the presence of co-infection (p value=0.228), although the result was not statistically significant. Conclusion : There is a correlation between CD4 Count and Dry Eye Disease severity among HIV patients. The lower the CD4, the higher the risk for HIV patients to get severe dry eye disease. This shows the importance of CD4 control and monitoring to prevent various ocular disease and manifestations related to HIV.